A novel fluorescent sensor based on sulfur and nitrogen co-doped carbon dots with excellent stability for selective detection of doxycycline in raw milk. Issue 21 (23rd February 2017) - Song, Jinping; Li, Jing; Guo, Ziying; Liu, Wen; Ma, Qi; Feng, Feng; Dong, Chuan
Abstract : Sulfur and nitrogen co-doped carbon dots obtained from casein exhibited excellent sensitivity and selectivity for the detection of doxycycline. Abstract : Casein was employed for the first time as a green carbon source to prepare water-soluble sulfur and nitrogen co-doped carbon dots (S, N-CDs). The as-synthesized S, N-CDs were characterized by transmission electron microscopy, X-ray photoelectron spectroscopy, UV-Vis absorption spectroscopy, and fluorescence spectroscopy. Results showed that the as-prepared S, N-CDs had excellent stabilities under various external conditions, such as high ionic strength, different pH levels, UV light irradiation, and long storage duration. More importantly, we found that doxycycline (Dox) could result in an effective fluorescence quenching of S, N-CDs via a static quenching process. Thus, a sensitive and selective sensing system for Dox detection was developed. The linear range was 1.0 × 10 −7 M to 1.0 × 10 −4 M, and the detection limit was 25 nm. Furthermore, the proposed sensing system successfully detected Dox in raw milk samples. This research will demonstrate the feasibility and potential applications of carbon nanomaterials in food and medical monitoring fields.